Chronic copper exposure exacerbates both amyloid and tau pathology and selectively dysregulates cdk5 in a mouse model of AD - Kitazawa, Masashi (2009)
Excess copper exposure is thought to be linked to the development of Alzheimer disease (AD) neuropathology. However, the mechanism by which copper affects the central nervous system remains unclear. To investigate the effect of chronic copper exposure on both beta-amyloid and tau pathologies, we treated young triple transgenic (3xTg-AD) mice with 250 ppm copper-containing water for the period of 3 or 9 months. Copper exposure resulted in altered APP processing; increased accumulation of the amyloid precursor protein (APP) and its proteolytic product, C99 fragment, along with increased generation of amyloid-beta peptides and oligomers. These changes were found to be mediated via upregulation of BACE1 as significant increases in BACE1 levels and deposits were detected around plaques in mice following copper exposure. Furthermore, tau pathology within hippocampal neurons was exacerbated in copper-exposed 3xTg-AD group. Increased tau phosphorylation was closely correlated with aberrant cdk5/p25 activation, suggesting a role for this kinase in the development of copper-induced tau pathology. Taken together, our data suggest that chronic copper exposure accelerates not only amyloid pathology but also tau pathology in a mouse model of AD.